Modified parallel hybrid heuristic for U.P. Integrated School and U.P. Pampanga timetabling - Avante, Raquel M (October 2004.)
This paper uses a parallelized hybrid heuristic, which is parallelizing hybrid genetic algorithm and simulated annealing, as an optimization technique to solve the school timetabling problem with actual data sets coming from the High School Department of the University of the Philippines Integrated School and U.P. Extension Program in Pampanga...
"October 2004."
Thesis (M.S. Applied Mathematics) -- University of the Philippines Diliman.
Keywords: University of the Philippines Integrated School; University of the Philippines (Pampanga); Schedules, School -- Automation; School day -- Planning -- Automation; Electronic data processing -- Education; Heuristic programming; Algorithms; Computer scheduling; Genetic programming (Computer science)